Issues in training and development - Husain, Saadat, 1946- (Dhaka : New Age Publications, 2002)
Articles on socio-economic conditions and the role of training in governance in Bangladesh.
Includes bibliographical references.
Keywords: Bangladesh -- Economic conditions; Bangladesh -- Social conditions; Bangladesh -- Politics and government